2017
DOI: 10.14260/jemds/2017/1488
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Colposcopy Using Swede Score in Screening of Cervical Cancer

Abstract: BACKGROUND Cervical cancer is a global health problem. It ranks as the 4 th leading cause of female cancer in the World, (1) the 2 nd leading cause of female cancer in India and the 2 nd most common female cancer in the women aged 15 to 44 years in World (1) and India. About 527,624 new cases are diagnosed and 265,672 cervical cancer deaths occur annually in the World. Incidence and prevalence of cervical cancer remains high in developing countries due to lack of resources, lack of effective screening programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…26 Penumalli et al reported in their study that according to histopathology, 144 (65.45%) were benign, showing chronic cervicitis, whereas 52 (23.64%) and 24 (10.9%) cases were diagnosed as CIN 1 (LGL) and HGL (CIN 2, CIN 3) respectively. 28 Biopsy was normal in 16 (3.0%) women. 31 Penumali et al did another study on 220 women and found that 52 (26.64%) and 24 (10.9%) were diagnosed with CIN1 and CIN2, 331.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…26 Penumalli et al reported in their study that according to histopathology, 144 (65.45%) were benign, showing chronic cervicitis, whereas 52 (23.64%) and 24 (10.9%) cases were diagnosed as CIN 1 (LGL) and HGL (CIN 2, CIN 3) respectively. 28 Biopsy was normal in 16 (3.0%) women. 31 Penumali et al did another study on 220 women and found that 52 (26.64%) and 24 (10.9%) were diagnosed with CIN1 and CIN2, 331.…”
Section: Resultsmentioning
confidence: 97%
“…26 The median (IQR) age at the first marriage of the patients was 17 (15)(16)(17)(18) years (range: 13-27), and the age at the first delivery of the patients was 19 (17)(18)(19)(20) years (range: 15-29). 28 Penumalli et al reported that the mean age at marriage was 19.2 years; 76.8% (n=169) had their marriage by 20 years. The 50.5% (111) had >25 years of married life.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations